NONALCOHOLIC FATTY LIVER DISEASE AND ALBUMINURIA : A SYSTEMATIC REVIEW - Nur Amelia, Devita (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: The presence of fat storage in the liver that is larger than 5% of the liver's weight is diagnostic of nonalcoholic fatty liver disease (NAFLD), which can occur in the absence of excessive alcohol consumption or a secondary cause of liver illnesses. It is interesting to note that it has been hypothesised that NAFLD might be able to contribute to albuminuria by exacerbating the endothelial dysfunction that results from systemic inflammation.Aim: This article examines the link between nonalcoholic fatty liver disease and albuminuria. Methods: This study showed that it met all of the requirements by looking at the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. So, the experts could make sure that the study was as current as possible. The search method used a number of electronic reference databases, such as Pubmed and SagePub, to look for papers that were published between 2000 and 2023. We didn't look at review papers, articles that had already been published, or articles that were only half done. Result: In the PubMed database, the results of our search brought up 89 articles, whereas the results of our search on SagePub brought up 33 articles. The results of the search conducted for the last year of 2013 yielded a total of 22 articles for PubMed and 16 articles for SagePub. In the end, we compiled a total of 17 papers, 12 of which came from PubMed and five of which came from SagePub. We included seven research that met the criteria.Conclusion: Study has consistently shown that there is a correlation between NAFLD and albuminuria.